High incidence of occupational exposures among healthcare workers in Erbil, Iraq - Salih Hosoglu; Zana Ahmad; Mohammed Sami Tahseen; Zehra Diyar; Sami Selbes; Ali Colak (Journal of Infection in Developing Countries)
Introduction: The current status of percutaneous injury and mucous exposures (PMEs) of hospital workers and factors associated with the injuries have not been studied in Iraq. This study aimed to evaluate the epidemiology of PMEs with blood or body fluids that leads serious risks for healthcare workers (HCWs). Methodology: An analytic, cross-sectional survey study was conducted among HCWs in Erbil city center, Iraq. The study was performed at sevenhospitals, and 177 participants were included. The dependent variable was the occurrence of PMEs in the last year, and the independent variables were age, sex, occupation of HCWs, working site, and work duration. Results: A total of 177 HCW participants included 57 nurses/midwives (32.2%), 59 doctors (33.3%), 27 laboratory workers (15.3%), and 34 paramedics/multipurpose workers (19.2%) from seven hospitals. The study concluded that 67.8% of the participants reported at least one occupational PME in the last year. In all, 13.3/person/year PME incidents were reported for nurses, 9.74/person/year for paramedics/multipurpose workers, 6.71/person/year for doctors, and 3.37/person/year laboratory workers. The mean number of PME incidents was 8.91/person/year. HCWs showed 85.0% compliance with wearing mask in risky situations. The most dangerous action for occupational exposure was blood taking (39.0%). In the univariate analysis, none of the investigated variables were found to be significantly related to PME. Conclusions: Occupational injuries and exposures in Iraqi HCWs are extremely common; awareness about protection is not sufficient. Nurses were found to be the highest risk group among HCWs. Preventive actions should be taken to avoid infection.